2015
DOI: 10.1534/genetics.115.176867
|View full text |Cite
|
Sign up to set email alerts
|

Germ Cell Segregation from the Drosophila Soma Is Controlled by an Inhibitory Threshold Set by the Arf-GEF Steppke

Abstract: Germline cells segregate from the soma to maintain their totipotency, but the cellular mechanisms of this segregation are unclear. The Drosophila melanogaster embryo forms a posterior group of primordial germline cells (PGCs) by their division from the syncytial soma. Extended plasma membrane furrows enclose the PGCs in response to the germ plasm protein Germ cell-less (Gcl) and Rho1-actomyosin activity. Recently, we found that loss of the Arf-GEF Steppke (Step) leads to similar Rho1-dependent plasma membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…PGC cellularization requires the concerted action of many proteins that regulate the organization of the actin cytoskeleton, including Anillin, to mediate closure of the PB furrow (Field et al, 2005). Recent studies suggest that gcl could play a role in controlling the reorganization of the actin cytoskeleton during PB furrow closure via Anillin (Cinalli and Lehmann, 2013) and/or Steppke (Step), a recently identified antagonist of Rho1 (Lee et al, 2015). Loss of Step activity results in precocious cellularization in the soma, while overexpressing Step blocks PGC formation by a mechanism that involves antagonizing Gcl activity (Lee et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…PGC cellularization requires the concerted action of many proteins that regulate the organization of the actin cytoskeleton, including Anillin, to mediate closure of the PB furrow (Field et al, 2005). Recent studies suggest that gcl could play a role in controlling the reorganization of the actin cytoskeleton during PB furrow closure via Anillin (Cinalli and Lehmann, 2013) and/or Steppke (Step), a recently identified antagonist of Rho1 (Lee et al, 2015). Loss of Step activity results in precocious cellularization in the soma, while overexpressing Step blocks PGC formation by a mechanism that involves antagonizing Gcl activity (Lee et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, additional downstream signaling pathways may require ligand-induced Torso receptor activation. Candidates include the JAK/STAT pathway, which is activated in dominant gain-of-function alleles of Torso (Li et al, 2002), and the ARF-GEF Steppke, which has been recently identified as a negative regulator of PGC formation (Lee et al, 2015). It will be of interest to explore further whether and how these alternative pathways oppose PGC formation.…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila embryogenesis begins as a syncytium in which PM cleavage furrows transiently separate dividing somatic nuclei and then fully cellularize ~6000 nuclei to form the cellular blastoderm [ 11 13 ]. Step localizes to these cleavage furrows and uses its Arf-GEF activity to antagonize the Rho1-actomyosin pathway during two forms of cell division [ 14 , 15 ]. Step acts first to control primordial germ cell division from the syncytial soma, and without Step, the division occurs at ectopic sites [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Step localizes to these cleavage furrows and uses its Arf-GEF activity to antagonize the Rho1-actomyosin pathway during two forms of cell division [ 14 , 15 ]. Step acts first to control primordial germ cell division from the syncytial soma, and without Step, the division occurs at ectopic sites [ 15 ]. Then, Step continues to act during the syncytial nuclear divisions of the soma to prevent closure of cleavage furrows at their basal tips.…”
Section: Introductionmentioning
confidence: 99%